Inovasi Sistem Administrasi Manunggal Satu Atap (Samsat) Dalam Rangka Meningkatkan Pelayanan Kepada Masyarakat - Hilda Mayang Sari; Aldri Frinaldi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The type of research used is descriptive research with a qualitative approach. The purpose of this study was to find out the Innovation of One-Stop Single Administration System (Samsat) in the Context of Improving Services to the Community. The results of this study indicate that the Service Innovation for Motorized Vehicle Tax Payments through the Services of the Samsat office at the Kerinci Regency Regent's Office can be said to have been going well, but there are still some deficiencies and obstacles that occur. Weaknesses in Samsat office service innovation can be seen from the attribute theory of innovation, namely triability (possibility of trying). In the innovation attributes, it can be seen that the trial service and socialization carried out by the district Samsat Office were not optimal. This can be demonstrated by the small number of taxpayer reports in the Samsat office services. Supporting factors consist of socialization of services, cooperation of related parties, service locations, and procurement of complaints. While the inhibiting factors consist of internal factors and external factors.